In it but not yet of it: barriers in accessing information that hinder the settlement of internally displaced persons - Martinez, Jasmine G. (2022)
Background. This is a study of information access of internally displaced persons (IDPs) resettled by the Philippine government into their new homes in San Jose Del Monte Heights, located in the City of San Jose Del Monte, Bulacan, Central Luzon.